Machine learning autonomous identification of magnetic alloys beyond the Slater-Pauling limit - Yuma Iwasaki (Nature Portfolio, 2021)
Finding materials with large magnetization is highly desirable for technological applications. Here, a machine learning autonomous search and automated combinatorial synthesis reveal that multi-element alloys with Ir and Pt impurities have a magnetization exceeding the Slater-Pauling limit of Fe75Co25.